PERSEPSI PESERTA DIDIK TENTANG PENTINGNYA BELAJAR BAHASA JERMAN DI ERA GLOBALISASI - Ida Costansa Tamaela; Eldaa Crystle Wenno; Piet Soumokil (German für Gesellschaft (J-Gefüge), 2022)
The purpose of this virtual outreach activities at SMAN 4 Masohi, Central Maluku district, with the theme "The Importance of Learning German in the Era of Globalization." This activity drew a total of 28 participants, including 1 German teacher, 19 science students, 1 alumni who were in Germany, 3 alumni who had passed to work in Germany, 1 German Language Study Program student who had achieved, and 3 German Language Study Program lecturers. The method used in the socialization activity is interactive, namely, the presentation of material is delivered alternately by all members of the socialization team of the German Language Education Study Program by creating interactive and educative situations in the form of discussions and questions and answers. In addition to providing students with an understanding and awareness of the importance of learning German in the age of globalization.This activity was enthusiastically welcomed by the students. It can be seen from the results of the answers given that this socialization activity has changed the perception of students who previously did not know what to know and increased students' insight about the importance of learning German in the era of globalization